Adjuncts to transcatheter aortic valve implantation. (4th May 2017) - McConkey, HZR; Arri, SS; Joseph, JP; Prendergast, BD; Redwood, S
ABSTRACT: Introduction : The appreciable rise in percutaneous valve procedures has been pursued by a wave of development in advanced technology to help guide straightforward, streamlined and safe intervention. This review article aims to highlight the adjunctive devices, tools and techniques currently used in transcatheter aortic valve implantation procedures to avoid potential pitfalls. Areas covered : The software and devices featured here are at the forefront of technological advances, most of which are not yet in widespread use. These products have been discussed in national and international structural intervention conferences and the authors felt it important to showcase particularly well designed adjuncts that improve procedural efficacy and safety. Whilst vascular pre-closure systems are used routinely and are an integral part of these complex cardiovascular procedures, these have been well summarised elsewhere and are beyond the scope of this article. Expert commentary : The rising volume of patients with aortic stenosis who are treatable with TAVI means that this exponential increase in procedures must be accompanied by a steady decline in procedural complications. This section provides an overview of our current perspective, and what we feel the direction of travel will be.